Secular trends in heart rate in young adults, 1949 to 2004: analyses of cross sectional studies. Issue 4 (13th September 2005) - Black, A; Murray, L; Cardwell, C; Davey Smith, G; McCarron, P
Abstract : Objective: To investigate secular trends in resting heart rate in young adults. Design, setting, and participants: A series of cross sectional cohorts of first year undergraduates (5562) aged 16–24 years who attended Queen's University Belfast from 1949 to 2004 and underwent health checks at the university health centre. Main outcome measure: Resting heart rate. Results: Crude aggregate data for 1949–59 showed a secular decline in heart rate in male and female students. Both unadjusted and fully adjusted analyses of data from 1975 onwards—controlled for age, body mass index, height, and smoking—showed a U shaped association between heart rate and year of entry to university in both sexes (p < 0.001): heart rate initially declined and then increased from the mid 1980s. Trends were similar in smokers and non-smokers and in students with normal body size and those who were overweight. However, heart rate in the 693 (28%) male students reporting the most physical activity remained stable and lower than that of men who participated in less physical activity over the period of the study. Similarly in female students, heart rate was generally lower in the 210 (10%) who participated in the most physical activity than in those who engaged in less physical activity. Conclusions: The decline in heart rate in young adults occurring at least 50 years ago and continuing until the 1980s is consistent with other favourable findings on cardiovascular health in this age group and with observed long term declines in cardiovascular mortality. The more recent rise in heart rate, not accounted for by increases in overweight, prompts concern that recent favourable trends in cardiovascular disease risk may not be maintained. Among students who took part in the highest levels of physical activity the finding of low and stable heart rates points to the importance of exercise in maintaining cardiovascular health. Measurement of heart rate in population surveys would provide a simple tool to assist monitoring cardiovascular health.